Identify the Cause of Inpatient Complaints at Islamic Hospital Surabaya Ahmad Yani Using Root Cause Analysis Method - Ayu Astiria Maya Asterix; Budhi Setianto; Inge Dhamanti (Media Gizi Kesmas, 2022)
Background: Surabaya Islamic Hospital is under the auspices of the Surabaya Islamic Hospital Foundation (YARSIS). In 2019, there were 559 complaints reported by PR staff. Meanwhile, during the pandemic in 2020 there was a decrease in complaints because there were only 261 customers who submitted complaints about the services they received at the Surabaya Islamic Hospital. Objectives: The general objective of this study was to identify the cause of patient complaints in the inpatient setting of the Surabaya Islamic Hospital using Root Cause Analysis (RCA) Methods: Researchers collect data through Surabaya Islamic Hospital complaint data in 2020. The data is processed through simple RCA stages and analyzed with fishbone diagrams for determining the root cause. Results: The results of the Root Cause Analysis of the complaints of inpatients at the Surabaya Islamic Hospital prove that there are at least 8 root problems and 6 solutions that can be done to overcome them. The most interventions/improvements must be carried out in the HR sector, namely the level of discipline, skills, empathy, communication, and the limitations of medical and non medical staff. The development of an Integrated Hospital Management Information System is also feasible to be implemented to provide more effective and efficient services. In addition, improvements in supporting facilities and enforcement of rules for inpatient visitors will make visitors feel more comfortable in the inpatient room. Conclusions: It is important for hospital to analyze the complaints received. The results of this study can be used by hospitals in Indonesia as references to improve their services.